Biochemical profile and in vitro neuroprotective properties of Carpobrotus edulis L., a medicinal and edible halophyte native to the coast of South Africa - Rocha, M. I. (2019)
This work reports the nutritional profile and in vitro neuroprotective properties of leaves of Carpobrotus edulis L, a medicinal and edible succulent species native to the coast of South Africa. Biomass was evaluated for proximate composition and for contents in carotenoids, liposoluble pigments and minerals. Hexane, dichloromethane, ethyl acetate and methanol extracts were prepared by Soxhlet extraction from dried biomass and evaluated for in vitro inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), capacity to attenuate hydrogen peroxide (H2O2)-induced injury in the human dopaminergic cell line SH-SY5Y and for anti-neuroinflammatory potential on lipopolysaccharide (LPS)-stimulated microglia cells. Extracts were evaluated for antioxidant activity by four complementary methods, total content of phenolics, tannins and flavonoids. Finally the profile of the main phenolic compounds was determined by high performance liquid chromatography with diode array detection (HPLC-DAD). C edulis has a high moisture content, high levels of crude protein, fibre, ash, carotenoids, calcium and iron and a low fat level. The extracts were able to efficiently scavenge the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH), reduce iron and chelate copper and iron ions, and exhibited different levels of phenolic compounds in the order ethyl acetate > methanol > dichloromethane > hexane. The main compounds detected were gallic and salicylic acids and quercetin, all in the ethyl acetate extract. The extracts allowed a dual and potent inhibition of AChE and BuChE. The dichloromethane and methanol extracts had the strongest capacity to prevent cell death induced by H2O2, and the methanol extract had anti-neuronflammatory properties. All together our results suggest that consumption of leaves of C edulis can contribute for a balanced diet, and that they may add to the improvement of cognitive functions. It also suggests possible novel biotechnological applications of C. edulis such as source of molecules and/or products for the food and/or pharmaceutical industries. Studies aiming to the isolation and identification of the bioactive compounds are already in progress. (C) 2017 SAAB. Published by Elsevier B.V. All rights reserved.